Hematological Study of Spleenctomized Dog in Iraq (Medico Legal Update, 2020)
The effect of total and partial splenectomy on hematological value was studied on 12 healthy dogs, dividedinto two groups (A and B). The total splenectomy (group A) exhibited significant reduction (P < 0.05) in Hb,PCV, and total RBC count but increase in ESR values. It also resulted in persistent increase in total leukocyte,neutrophil, and lymphocyte counts. In partial splenectomy produced non-significant effects on hematologicalparameters. No significant alteration in serum glucose or total protein concentration was observed after totalor partial splenectomy.